«Owners of the sands»: sand protection works on the lands of the nomadic peoples of Southern Russia (Nogais, Kalmyks and Turkmens) in the XIX – early XX centuries - Aigul T., Dzhumagulova (Kavkazologiya, 2024)
The publication examines the organization of sand protection works carried out in semi–desert zones of Southern Russia in the XIX - early XX centuries. Despite separate publications on measures to combat desertification in the Russian Empire, sand protection activities that unfolded in the XIX – early XX centuries on the lands of the nomadic peoples of Southern Russia (Nogais, Kalmyks and Turkmens) did not become the subject of separate works, which determines the nov-elty of the study. The peculiarities of the natural, climatic and geographical living conditions of nomads and their irrational use of arid zones as pasture lands for their livestock were factors that caused the rapid growth of sands in the XIX – early XX centuries. Sand protection works in the south and officials of the sand-ravine parties and the corps of foresters of the Forest Department, under the jurisdiction of the Ministry of State Property, carried south-east of Russia out. The ac-tivities of sand protection organizations included experimental measures to combat desertifica-tion, which included husking and grass sowing on the sands, sowing sandy oats, removing sands from the use of their owners, forestry and horticulture in the steppe. The source base of the study was materials extracted from the State Archives of the Stavropol Territory (GASK) funds: 153 «Forester of the Stavropol sandy-ravine district» and 247 «Stavropol Provincial Forest Protection Committee». Historiographical works on the study of the problem include publications by pre–revolutionary, Soviet and modern researchers involved in combating desertification in Southern Russia in the XIX - early XX centuries. The analysis of materials and sources made it possible to trace the peculiarities of the activities of central and regional authorities, local societies (A.D. – owners of sands), and other organizations that participated in sand protection works during the historical period under consideration. The conclusion is formulated that the sand protection activi-ty that unfolded in the South of Russia in the XIX – early XX centuries. It included many forest reclamation works, the purpose of which was to curb the process of desertification of pasture and agricultural lands of Nogais, Kalmyks and Turkmens, which in turn was a measure of protection and guardianship of the life, health and economic and cultural activities of nomadic peoples with-in the Russian Empire.